Resolution of Environmental Pollution Cases Due to Sand Mining Waste in Glandang Village, Pemalang Regency - Rianto, Dika Lufi (UMPurwokerto Law Review, 2022)
<span lang="IN" style="font-size: 8.0pt; line-height: 115%; font-family: ’Book Antiqua’,serif; mso-fareast-font-family: Calibri; mso-bidi-font-family: Arial; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: BN;">Abstract <span lang="IN" style="font-size: 8.0pt; line-height: 115%; font-family: ’Book Antiqua’,serif; mso-fareast-font-family: Calibri; mso-bidi-font-family: Arial; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: BN; mso-bidi-font-weight: bold;">Environmental problems are multidimensional problems involving various groups. Even so, humans still play an essential role in solving environmental problems; the issue of environmental problems becomes essential because problems in the environment affect the quality of life of humans and other creatures in the future. Environmental problems often occur due to activities carried out by humans in utilizing natural resources to gain profits, such as mining. This research aims to find out how to solve environmental pollution problems and the inhibiting factors for resolving environmental pollution. <span lang="EN-US" style="font-size: 8.0pt; line-height: 115%; font-family: ’Book Antiqua’,serif; mso-fareast-font-family: Calibri; mso-bidi-font-family: Arial; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: BN; mso-bidi-font-weight: bold;">T<span lang="IN" style="font-size: 8.0pt; line-height: 115%; font-family: ’Book Antiqua’,serif; mso-fareast-font-family: Calibri; mso-bidi-font-family: Arial; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: BN; mso-bidi-font-weight: bold;">his research <span lang="EN-US" style="font-size: 8.0pt; line-height: 115%; font-family: ’Book Antiqua’,serif; mso-fareast-font-family: Calibri; mso-bidi-font-family: Arial; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: BN; mso-bidi-font-weight: bold;">used<span lang="EN-US" style="font-size: 8.0pt; line-height: 115%; font-family: ’Book Antiqua’,serif; mso-fareast-font-family: Calibri; mso-bidi-font-family: Arial; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: BN; mso-bidi-font-weight: bold;"> <span lang="IN" style="font-size: 8.0pt; line-height: 115%; font-family: ’Book Antiqua’,serif; mso-fareast-font-family: Calibri; mso-bidi-font-family: Arial; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: BN; mso-bidi-font-weight: bold;">the normative juridical<span lang="EN-US" style="font-size: 8.0pt; line-height: 115%; font-family: ’Book Antiqua’,serif; mso-fareast-font-family: Calibri; mso-bidi-font-family: Arial; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: BN; mso-bidi-font-weight: bold;"> method<span lang="IN" style="font-size: 8.0pt; line-height: 115%; font-family: ’Book Antiqua’,serif; mso-fareast-font-family: Calibri; mso-bidi-font-family: Arial; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: BN; mso-bidi-font-weight: bold;">, which conceptualizes the law as what is written in the rules and regulations<span lang="EN-US" style="font-size: 8.0pt; line-height: 115%; font-family: ’Book Antiqua’,serif; mso-fareast-font-family: Calibri; mso-bidi-font-family: Arial; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: BN; mso-bidi-font-weight: bold;">. T<span lang="IN" style="font-size: 8.0pt; line-height: 115%; font-family: ’Book Antiqua’,serif; mso-fareast-font-family: Calibri; mso-bidi-font-family: Arial; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: BN; mso-bidi-font-weight: bold;">he data collection method in this study uses primary and secondary legal materials to uphold research as well as identify and clarify legal facts by asking questions. to sources according to research needs. Based on the data analysis, there are efforts to resolve environmental pollution caused by sand mining, namely the creation of a shelter as a place for waste disposal, as well as covering a tarpaulin <span lang="EN-US" style="font-size: 8.0pt; line-height: 115%; font-family: ’Book Antiqua’,serif; mso-fareast-font-family: Calibri; mso-bidi-font-family: Arial; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: BN; mso-bidi-font-weight: bold;">on<span lang="IN" style="font-size: 8.0pt; line-height: 115%; font-family: ’Book Antiqua’,serif; mso-fareast-font-family: Calibri; mso-bidi-font-family: Arial; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: BN; mso-bidi-font-weight: bold;"> sand vehicles so as not to cause dust, as well as inhibiting factors in resolving cases of environmental pollution. Two factors, namely from the community and the Pemalang Regency Environmental Service, from the community that the community is less active by not reporting if there is environmental damage, and from the Environmental Service the lack of personnel handling related cases to environmental pollution. <span lang="IN" style="font-size: 8.0pt; line-height: 115%; font-family: ’Book Antiqua’,serif; mso-fareast-font-family: Calibri; mso-bidi-font-family: Arial; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: BN; mso-bidi-font-weight: bold;">Keywords: first keyword, second keyword, third keyword <span lang="IN" style="font-size: 8.0pt; line-height: 115%; font-family: ’Book Antiqua’,serif; mso-fareast-font-family: Calibri; mso-bidi-font-family: Arial; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: BN; mso-bidi-font-weight: bold;"> <span lang="IN" style="font-size: 8.0pt; line-height: 115%; font-family: ’Book Antiqua’,serif; mso-fareast-font-family: Calibri; mso-bidi-font-family: Arial; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: BN; mso-bidi-font-weight: bold;">Abstrak Permaslahan lingkungan merupakan permasalahan multidimensi yang melibatkan berbagai kalangan. Meskipun begitu manusia tetap berperan penting untuk menyelesaikan permasalahan lingkungan, isu permasalahan lingkungan menjadi penting karena permasalahan terhadap lingkungan mempengaruhi kualitas hidup manusia dan makhluk lain di masa mendatang. Permasalahan lingkungan kerap terjadi karena aktivitas yang dilakukan manusia dalam memanfaatkan sumber daya alam untuk memperoleh keuntungan seperti pertambangan. Tujuan dari penelitian ini untuk mengetahui bagaimana upaya dalam menyelesaikan permasalahan yang berkaitan dengan pencemaran lingkungan dan apa faktor pengahambat upaya penyelesaian terhadap pencemaran lingkungan. Adapun metode yang digunakan dalam penelitian ini adalah yuridis normatif, dimana hukum dikonsepkan sebagai apa yang tertulis dalam peraturan perundang-undangan, dan metode pengumpulan data dalam penelitian ini menggunakan bahan hukum primer dan sekunder untuk menjunjung penelitian serta identifikasi dan klarifikasi fakta hukum dengan cara mengajukan pertanyaan kepada narasumber sesuai dengan kebutuhan penelitian. Berdasarkan dari analisis data yang digunakan penelitian ini memperoleh upaya penyelesaian terhadap pencemaran lingkungan yang di disebabkan oleh pertambangan pasir, yaitu dibuatnya penampungan sebagai tempat pembuangan limbah, serta penutupan terpal terhadap kendaraan pasir agar tidak menimbulkan debu, adapaun faktor pengahambat dalam upaya penyelesaian kasus pencemaran lingkungan terdapat dua faktor yaitu dari masyarakat dan Dinas Lingkungan Hidup Kabupaten Pemalang, dari masyarakat kurang aktifnya masyarakat dengan tidak melapor apabila terjadi kerusakan lingkungan, dan dari Dinas Lingkungan Hidup kurangnya personil dalam menangani kasus terkait pencemaran lingkungan. Kata Kunci : Penggolongan, Surat Keterangan Waris, Diskriminasi